MENGUNGKAP POTENSI SELF-EFFICACY MELALUI ANALISIS LITERATUR DALAM PEMBELAJARAN MATEMATIKA - Gusteti, Meria Ultra; Rahmalina, Widdya; Azmi, Khairul; Mulyati, Asrina; Wulandari, Suci; Hayati, Rahmatul; Fajriah, Nur Azizah (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This literature research examines the concept of self-efficacy in technology-integrated mathematics learning and its impact on student achievement. Self-efficacy, a person's confidence in completing a task or achieving a result, is closely related to mathematical achievement, especially with the use of technology as a learning tool. Students with high self-efficacy tend to be more accomplished, motivated, and committed to technology-based learning. Strategies to increase student self-efficacy include constructive feedback via digital platforms, student-focused, technology-based learning approaches, and the application of real-life relevant tasks using simulations and technology applications. This strategy reinforces students' confidence in their math skills, motivating learning in a digital environment. The role of parents is also important, where their support and positive expectations, channelled through technology, increase students' self-efficacy. Parents' perceptions of the integration of technology in schools have a direct impact on students' self-efficacy, affirming the need for cooperation between schools, technology, and parents in mathematics education. Based on the findings, education practitioners are advised to integrate technology, provide supportive feedback, implement technology-based learning strategies, and collaborate schools with parents using digital platforms. In conclusion, a holistic approach involving self-efficacy, multi-stakeholder engagement, and technology integration is necessary for the success of mathematics education.